146k views
2 votes
Use the table below to answer this question

find the average rate of change for the given function from x=0 to x=2​

Use the table below to answer this question find the average rate of change for the-example-1
User Tesicg
by
4.5k points

1 Answer

4 votes

Answer:

-4

Explanation:

Average rate of change from x = 0 to x = 2:

Average rate of change =
(f(b) - f(a))/(b - a)

Where,


a = 0, f(a) = 2


b = 2, f(b) = -6

Plug in the values into the formula for average rate of change.


= (-6 - 2)/(2 - 0)


= (-8)/(2)


= -4

Average rate of change from x = 0 to x = 2 is -4

User VLXU
by
5.7k points